Housing wealth and aged care: asset-based welfare in practice in three OECD countries - Wood, Gavin; ViforJ, Rachel; Haffner, M.E.A. (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2020)
The transition of the baby boomer bulge into old age and their increasing longevity will lift the numbers of elderly in residential aged care. Population ageing and associated fiscal pressures have motivated governments to shift responsibility for the financing of aged care to the individual. We consider policies that include owner-occupiers’ housing wealth and imputed rental incomes in means tests that determine co-contribution charges for residential aged care. Differences in how housing wealth is included in the residential aged care resource tests of three OECD countries–Australia, England and the Netherlands–are documented. We find some neglected equity implications as tenants in all three countries typically pay higher co-payments for their residential aged care than homeowners with similar wealth holdings. These outcomes are a consequence of the concessional treatment of owners’ housing equity stakes, and of wider significance given the growing importance of asset-based welfare strategies. England has relatively progressive asset and income tests that offer more limited concessions.